Assessment of the Impact of Different Types and Intensities of Physical Exercise on the Quality of Life of Patients with Alzheimer’s Disease: A Literature Review - Barabasz, Katarzyna; Więcławek, Paulina; Juda, Piotr; Kłaptocz, Patrycja; Łukoś-Karcz, Katarzyna; Bańkowski, Dominik; Pabian, Gabriela; Musiał, Karol; Bielak, Kamil (Quality in Sport, 2025)
Objective Alzheimer’s Disease (AD) is the most common form of dementia, representing a global health challenge. The aim of this review is to assess the impact of different types and intensities of physical exercise on cognitive functions, biomarkers, and the quality of life of AD patients. Methods Studies from PubMed, Scopus, Cochrane Library, and Web of Science (2000–2024) were analyzed, focusing on the effects of aerobic, resistance, and combined exercises on memory, executive functions, biomarkers (amyloid beta, tau protein, BDNF), daily living abilities (ADL), and quality of life. The review included 42 studies, including randomized controlled trials and meta-analyses. Results Moderate-intensity aerobic and combined exercises improve memory and executive functions, while resistance training increases hippocampal volume, supporting spatial memory. High-intensity exercises boost BDNF levels, and moderate-intensity exercises reduce neurodegenerative biomarkers and improve ADL. Conclusions Moderate aerobic and combined exercises are effective in preventing and supporting AD therapy. Further research is needed to standardize exercise protocols and evaluate their long-term effects.